A highly proton-conducting, methanol-blocking Nafion composite membrane enabled by surface-coating crosslinked sulfonated graphene oxide. Issue 10 (4th January 2016) - He, Guangwei; He, Xueyi; Wang, Xinglin; Chang, Chaoyi; Zhao, Jing; Li, Zongyu; Wu, Hong; Jiang, Zhongyi
Abstract : Coating an ultrathin graphene oxide film onto a Nafion membrane confers a distinct anti-tradeoff behavior: 93% decrease of methanol permeability while retaining the high proton conductivity. Abstract : Coating an ultrathin crosslinked graphene oxide film onto a Nafion support enables the tradeoff effect to be successfully overcome by the resulting composite membrane: 93% decrease of methanol permeability while retaining the high proton conductivity of Nafion, owing to the synergistic modulation of methanol-transport and proton-transport channels within the graphene oxide film.